Automated testing tools for mobile applications - Saad, Nurul Husna; Awang Abu Bakar, Normi Sham (2014)
Software Testing is known as an important part in software development as the product needs to meet the user’s expectations and requirements. The testing tool is developed along with the development of automated software testing to act as a medium to test the software, and the existence of these tools eventually cut down the human’s effort, energy, and time. Software testing tools are the key assets of a project that can improve productivity and software quality. As there are many tools in the market nowadays, the process of selecting the tool should be explained in detail and specific towards its functions and efficiency. This paper aims to compare the test automation tools and finally chose the most suitable tool according to our research needs.